The economic burden of EU ETS2 carbon pricing on single and childless households: focusing on transport and building sectors - Cui, Yalei; Wu, Wensen (Frontiers in Environmental Science, 2025)
The EU’s extension of emissions trading to buildings and road transport via the second Emissions Trading System (ETS2) marks a critical juncture in climate policy. While carbon pricing is essential for achieving ambitious climate goals, its implementation poses significant social equity challenges. This study fills a gap in the literature by utilizing a Multiregional input-output (MRIO) model to analyze the economic impact of EU ETS2-based carbon pricing on single and childless households. Our findings indicate that these households disproportionately bear the carbon costs burden under EU ETS2, with notable regional variations. Households in economically disadvantaged areas or those with less robust social welfare systems experience more severe financial burdens. Crucially, substantially higher carbon expenditure on residential heating fuels imposes critical pressure, forcing single and childless households to reduce spending on other essentials, such as food, to maintain heating. Furthermore, simulations of carbon revenue rebates demonstrate that average per-household rebates and targeted heating fuel subsidies offer greater protection for vulnerable households. This study highlights the necessity for targeted policies to mitigate the economic pressures on single and childless households associated with carbon pricing’s focus on the transport and building sectors.